POTENSI PEMANFAATAN DAUN SINGKONG (Manihot utilissima) TERFERMENTASI SEBAGAI BAHAN PAKAN UNTUK MENINGKATKAN PERTUMBUHAN IKAN MAS (Cyprinus carpio) - Alfirah Nurul Aisyah; Dewi Nur'aeni Setyowati; Baiq Hilda Astriana (Universitas Mataram, 2021)
This study heads to analyze the effect of adding fermented cassava’s leaf flour in artificial feed on the growth of carp and optimum concentration to produce growth and a high survival rate for carp. The method used in this study is an experimental method with a Completely Randomized Design (CDR) using 5 treatments and 3 replications. The treatment that was tried was the addition of fermented cassava leaf flour by 10%, 15%, 20%, 25% and 0% without fermentation of cassava leaves. The parameters observed in this study were absolute growth rate, specific growth rate, survival rate (SR), feed conversion ratio and feed efficiency. The results of analysis of variance (ANOVA) on absolute growth and specific growth rate differ significant (P<0,05) and give no significant difference (P> 0,05) on survival rate, Feed Conversion Ratio and Food Efficiency.